2011
DOI: 10.1002/tea.20449
|View full text |Cite
|
Sign up to set email alerts
|

Feeling of certainty: Uncovering a missing link between knowledge and acceptance of evolution

Abstract: We propose a new model of the factors influencing acceptance of evolutionary theory that highlights a novel variable unexplored in previous studies: the feeling of certainty (FOC). The model is grounded in an emerging understanding of brain function that acknowledges the contributions of intuitive cognitions in making decisions, such as whether or not to accept a particular theoretical explanation of events. Specifically, we examine the relationships among religious identity, level of education, level of knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 70 publications
(104 reference statements)
2
81
0
2
Order By: Relevance
“…For instance, the measure of acceptance of evolutionary theory (MATE) (Rutledge and Warden 1999) is widely used to measure acceptance (Akyol et al 2012;Barone et al 2014;Carter and Wiles 2014;Ha et al 2012), however, many items on this scale conflate acceptance with understanding (Glaze and Goldston 2015;Smith 2009). …”
Section: Belief Understanding Acceptance and Knowledgementioning
confidence: 99%
“…For instance, the measure of acceptance of evolutionary theory (MATE) (Rutledge and Warden 1999) is widely used to measure acceptance (Akyol et al 2012;Barone et al 2014;Carter and Wiles 2014;Ha et al 2012), however, many items on this scale conflate acceptance with understanding (Glaze and Goldston 2015;Smith 2009). …”
Section: Belief Understanding Acceptance and Knowledgementioning
confidence: 99%
“…This is a difficult task, and not without substantial conceptual and methodological obstacles, as Ha et al (2012) have shown that students have difficulty with tracings of their thinking and reasoning processes and may not be metacognitively aware of the origins of their thoughts and beliefs. With this cautionary note in mind, however, it is nonetheless important to ask students with varying positions on evolution, especially those who may have recently changed or may be in the process of changing their minds regarding evolution, which factors they perceive to influence their thinking.…”
Section: Teaching Toward Acceptancementioning
confidence: 99%
“…Smith (1994) posits that the distinction between belief (when meaning subjective and based on personal conviction) and acceptance (when meaning a systematic evaluation of the evidence) is a crucial aspect of understanding the nature of scientific knowledge. Ha et al (2012) agree with such careful and deliberate use of language in science classrooms, but they posited that it is more important to help students understand the "multiple meanings and applications" (p. 99) of words, especially in the context of science. In a very well-reasoned discussion, Ha et al (2012) introduced a new concept in this discussion, the Feeling of Certainty (FOC), which they characterize as representing a cluster of related mental states that "emerges involuntarily without prior, conscious cognition…in association with conscious thoughts" (p. 98).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ha, Haury and Nehm (2012) stated that "believing, knowing and accepting are intimately related terms, all having a form of belief as a component" (p. 97). Cobern (1996) stated that knowing is the metaphysical process by which one accepts a comprehended concept as true or valid.…”
Section: Belief and Understandingmentioning
confidence: 99%